Pesan Dakwah Visual Pada Kalangan Millenial Melalui Akun Instagram @Sketsadakwahh (Analisis Teori Semiotika Roland Barthes) - Nur Aminah Munthe; Nunu Burhanuddin (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
Instagram is a social media application that has uses for taking photos, sharing photos in various forms and sharing information with its users. Da'wah delivery can be utilized in the Instagram application media, namely visual da'wah messages where the delivery process uses visuals (images) contained on the Instagram account @sketsadakwahh. Images can convey messages or information to its users. Which account is more dominant among millennials to access. The research conducted by the author aims to find out how Da'wah messages are on the Instagram account @sketsadakwahh by using Roland Barthes' Semiotic Theory Analysis. This research is used by the author is a qualitative approach which aims to be able to understand the phenomena that exist in the object being studied and this research does not require statistical analysis but words or speech on the Instagram account @sketsadakwahh.